Chymotrypsin inhibitor activity in winged beans (Psophocarpus tetragonolobus) - Tan, Nget-Hong; A. Rahim, Zubaidah; Khor, Hun-Teik; Wong, Kai-Choo (American Chemical Society, 1984)
Chymotrypsin inhibitor activity of winged beans (Psophocarpus tetragonolobus) was investigated. Extractability of the inhibitors by aqueous solution increases with increasing pH. The chymotrypsin inhibitor activity in winged bean meal was extremely resistant to dry heat treatment. Prolonged boiling (60 min) of the bean was required to destroy the inhibitor activity. Autoclaving is more effective in destroying the chymotrypsin inhibitor activity in the bean meals: 20 min of autoclaving at 120 °C, 1.05 kg/cm2, generally destroyed more than 90% of the inhibitor activity. There are some varietal variations in the thermal stability of winged bean chymotrypsin inhibitor activity. The chymotrypsin inhibitor activity in the winged bean meal extract is heat labile.